Naringenin Induces Pathogen Resistance Against Pseudomonas syringae Through the Activation of NPR1 in Arabidopsis - An, Jonguk; Kim, Sun Ho; Bahk, Sunghwa; Vuong, Uyen Thi; Nguyen, Nhan Thi; Do, Huy Loc; Kim, Sang Hee; Chung, Woo Sik (Frontiers in Plant Science, 2021)
Flavonoids are well known for the coloration of plant organs to protect UV and ROS and to attract pollinators as well. Flavonoids also play roles in many aspects of physiological processes including pathogen resistance. However, the molecular mechanism to explain how flavonoids play roles in pathogen resistance was not extensively studied. In this study, we investigated how naringenin, the first intermediate molecule of the flavonoid biosynthesis, functions as an activator of disease resistances. The transcript levels of two pathogenesis-related (PR) genes were increased by the treatment with naringenin in Arabidopsis. Interestingly, we found that naringenin triggers the monomerization and nuclear translocation of nonexpressor of pathogenesis-related genes 1 (NPR1) that is a transcriptional coactivator of PR gene expression. Naringenin can induce the accumulation of salicylic acid (SA) that is required for the monomerization of NPR1. Furthermore, naringenin activates MPK6 and MPK3 in ROS-dependent, but SA-independent manners. By using a MEK inhibitor, we showed that the activation of a MAPK cascade by naringenin is also required for the monomerization of NPR1. These results suggest that the pathogen resistance by naringenin is mediated by the MAPK and SA dependent activation of NPR1 in Arabidopsis.